The many journeys of Journey to the West: establishing Chinese media industries in the globalised context - Zhang, Hening (2024)
Over the past century, the Chinese media industries have progressively become more prominent in carving out their spaces in the global media landscape in the 21st century. The emergence of the Chinese media industries is not only shaped by the internal relationship with the state and informed by specific historical, cultural, political and economic factors, but also reflects a set of responsive manoeuvres in response to the continuous, ever-changing influence of external competition from Europe and the US. A key recurring feature in the development of the Chinese media industries is how various sectors within these industries, such as film, television, theme parks, advertising and entertainment, have increasingly explored and capitalised on Journey to the West (JTTW), a culturally prominent Ming Dynasty literary classic. This has resulted in a wide array of screen adaptations, themed entertainment spaces and promotional content. Taking a media industry studies perspective, this thesis adopts a holistic and cross-sector approach to examine industries including film and television, theme parks, advertising and branded content in order to interrogate the cultural, political, economic and global-local dynamics that shape the strategic use of Journey to the West in these industries. Using diverse methods and evidence — including production discourse analysis, policy and document review and examination of trade press and promotional materials — this thesis begins with a historical overview of how JTTW contributed to the industrial localisation of Chinese film and television industries in the 20th century. This thesis then explores how film co-productions of JTTW involved a symbiotic relationship between Hong Kong and mainland film industries. By exploring the expansion of JTTW into themed environments, the thesis will examine how these spaces negotiate ‘Chineseness’, counter the influence of US cultural brands and inform local tourism policies and theme park industries development. Lastly, this thesis investigates the cultural and commercial exploitation of JTTW in branded entertainment, analysing how global brands and companies construct ideas of ‘Chineseness’ in order to operate in and navigate through China’s media and regulatory landscape. Ultimately, this thesis argues that Journey to the West has been strategically valuable to emergent Chinese media industries as it offers a way to negotiate ‘Chineseness’ in the face of global competition and the resulting complex interplay among cultural, political, economic and global-local dynamics.